Pengaruh Servant Leadership Terhadap Daya Saing Lulusan Pendidikan Islam di Era Persaingan Global: Perspektif Alumni - Moch. Zakki Mubarok (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
This study aims to analyze the effect of servant leadership on alumni competitiveness at SMA Darul Ulum 2 Unggulan BPPT Jombang Cambridge International School and to measure its impact on alumni perceptions regarding their readiness to face global competition. The research uses a quantitative method with a survey approach involving alumni as respondents. Data were collected through questionnaires designed to measure alumni's perceptions of the implementation of servant leadership at the school and its impact on their competitiveness. The findings show that the application of servant leadership at SMA Darul Ulum 2 Unggulan BPPT Jombang Cambridge International School has a significant positive impact on alumni competitiveness. Alumni exposed to this leadership style feel more prepared to face global challenges, both in terms of adaptability and relevant social skills for the workforce. Pearson's correlation analysis shows a strong relationship between servant leadership and alumni competitiveness. These findings suggest that leadership focused on service and individual development can enhance the quality of education and alumni competitiveness, preparing them to face global competition. This study contributes significantly to the development of educational management science, particularly in Islamic education, by demonstrating the importance of servant leadership in shaping competitive graduates who are ready to compete at a global level.